Վաղ շրջանի պատմագրությունը Գրիգոր Մագիստրոսի ստեղծագործություններում - Թեո Մաարտըն վան Լինտ («Նաիրի» հրատ.)
Grigor Magistros Pahlawuni had a keen interest in the past of his people, which manifests itself among other things in his quotations from Movsēs Xorenac‗i‘s History of the Armenians and from Agat‗angełos‘ History, and no less through his interest in folk-lore, which represents a rich source for ancient, sometimes pre-Christian tradition.
Keywords: Պատմագրություն